Effect of Annealing Temperature on the Structural and Optical Properties of CdS Thin Films Deposited by CBD - Ikball Ahamed E.M.K.; Sen Gupta A.K.; Khan M.N.I.; Matin M.A.; Amin N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Annealing; Buffer layers; Cadmium sulfide; Crystallinity; II-VI semiconductors; Infrared devices; Near infrared spectroscopy; Optical lattices; Optical properties; Thin film solar cells; Ultrathin films; Annealing temperatures; As-deposited films; Comparative studies; Effect of annealing; Electrical and optical properties; High transmittance; Structural and optical properties; Vacuum environment; Optical films